Տարբերակները հին հայերենի աստղատոմարական տերմինահամակարգում - Վ. Ս. Ավետիսյան (Հայկական ԽՍՀ գիտությունների ակադեմիա)
Вариативность терминов характерна главным образом для периода формирования терминологической системы, когда терминообразование еще происходит стихийно. The differentiation of terms is perfectly characteristic of the period of formation of terminological systems when term formations were still performed spontaneously.
Keywords: Astronomy; Science; Auxiliary Sciences of History; Philology; Linguistics; Language and Literature; Chronology; Calendar